Anion interaction with homoditopic chlorodiorganotin(IV) dithiocarbamate complexes derived from a naphthalene diimide. A pathway to obtain metallomacrocycles - Claudio Catalan, Miguel Angel (2020)
Four new homoditopic bis[chlorodiorganotin(IV) and triorganotin(IV) dithiocarbamate] complexes derived from naphthalene diimide (NDI) with general formula NDI-[(CH2)2-N(CH2Ph)(CS2SnR2X)]2, 3: R = n-Bu, X = Cl; 4: R = Me, X = Cl; 5: R = Ph, X = Cl; 6: R = X = Me; were prepared from triethylammonium ((1,3,6,8-tetraoxo-1,3,6,8-tetrahydrobenzo[lmn][3,8]phenanthroline-2,7-diyl)bis(ethane-2,1-diyl))bis(benzylcarbamodithioate) 2. All compounds were characterized by IR, as well as 1H and 13C NMR spectroscopy. The complexes 3–6 also were characterized by 119Sn NMR spectroscopy. In addition, complex 3 was further characterized by single-crystal X-ray diffraction analysis. The crystallographic study performed on complex 3 showed that the tin atom has a coordination geometry intermediate between square-pyramid and a trigonal-bipyramidal, with τ value of 0.69. In addition the presence of cooperative CH…π, CH…S, CH…O and S…π intramolecular interactions in the crystal structure of 3 was observed. The interaction of complexes 3–6 with anions (CH3CO2−, F−, H2PO4−) in CDCl3 was studied by UV/Vis, fluorescence and 119Sn NMR titrations. The addition of the foregoing anions to complexes 3-6 lead to the displacement of the chloride ligand at the tin(IV) atom. However, an the excess of F− or H2PO4− induced the self-assembly of complexes 3 and 5 in their corresponding binuclear metallomacrocycles.